SAT0143 SAFETY AND EFFECTIVENESS OF BIOLOGIC DISEASE-MODIFYING ANTIRHEUMATIC DRUGS IN ELDERLY PATIENTS WITH RHEUMATOID ARTHRITIS. (June 2019) - Freitas, Raquel; Fonseca, Joao Eurico; Polido-Pereira, Joaquim; Madeira, Nathalie; Miranda, Luís Cunha; Bernardes, Miguel; Fernandes, Bruno Miguel; Costa, Flavio; Santiago, Mariana; Neto, Agna; Azevedo, Soraia; Dias, João Madruga; et al.
Abstract : Background: Elderly population with rheumatoid arthritis (RA) is increasing. However, these patients are frequently excluded from clinical trials and data on effectiveness and safety of biologic Disease-Modifying Antirheumatic Drug (bDMARD) is scarce. Objectives: To assess the persistence of 1 st bDMARD and the effectiveness and safety of bDMARD among elderly (≥65 years). Methods: Prospective multicenter cohort-study of RA patients starting a 1 st bDMARD registered at Reuma.pt. Demographic and disease characteristics, comorbidities, medications, disease activity at baseline and follow up (3, 6 and 12 months) and adverse events (AE) were compared between elderly and adult (<65 years) patients. Treatment persistence was estimated using Kaplan-Meier analysis. Effectiveness was measured as EULAR crude response rates, LUNDEX corrected, and adjusted for baseline characteristics. Results: 2400 patients were included, of which 486 aged ≥65 years (table 1 ). Crude median persistence in bDMARD was 19.7 months (95%CI 14-25) in adults and 14.5 (95%CI 3-26) in elderly patients (log rank test, p=0.46) (figure 1 ). EULAR response (crude and LUNDEX corrected) was similar in the two groups at 3 and 6 months (figure 2 ). After adjustment for baseline characteristics, response rate was inferior in elderly at 12 months (p=0.01). There were 697 AE reported. Except for infections, more common in elderly patients (p=0.03), the rates of severe AE, opportunistic infection, allergic reactions, cancer or hospitalizations were similar in the two groups, as well as the time to 1 st AE occurrence (figure 2 ). Conclusion: Our findings showed that persistence of 1 st bDMARD was similar in adults and elderly RA patients. Though elderly had more severe disease and comorbidities at baseline, bDMARD treatment was equally effective and safe in the short term. However, it is necessary to consider the greater risk of infection in elderly when prescribing a biologic. Disclosure of Interests: None declared